2018
DOI: 10.1016/j.neuroscience.2018.02.043
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Expert’s Attention Superiority on Skill-related Scene Dynamic by the Activation of left Medial Frontal Gyrus: An ERP and LORETA Study

Abstract: Extensive studies have shown that a sports expert is superior to a sports novice in visually perceptual-cognitive processes of sports scene information, however the attentional and neural basis of it has not been thoroughly explored. The present study examined whether a sport expert has the attentional superiority on scene information relevant to his/her sport skill, and explored what factor drives this superiority. To address this problem, EEGs were recorded as participants passively viewed sport scenes (tenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The flanker effect reported by Horstmann et al [24] relying on the methodology devised by Ericksen and Ericksen [39] is linked to the emotional saliency of threat-related flankers, which increases the response time to stimuli presented as targets [3,67]. Here, we corroborated such an effect with an Emotional Flanker Task [27] and sought evidence of the neural underpinnings of such a threat-related attentional bias.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The flanker effect reported by Horstmann et al [24] relying on the methodology devised by Ericksen and Ericksen [39] is linked to the emotional saliency of threat-related flankers, which increases the response time to stimuli presented as targets [3,67]. Here, we corroborated such an effect with an Emotional Flanker Task [27] and sought evidence of the neural underpinnings of such a threat-related attentional bias.…”
Section: Discussionsupporting
confidence: 74%
“…Publications contributing evidence on covert/overt attention mechanisms, which are the most relevant to the present study, reported the use of a variety of stimuli including IAPS Images [33][34][35][36][37][38], Chinese proverbs [37], other affective pictures like sports or body expressions [39,40], arousing or aversive sounds with images [13,41,42], manipulated photos of participants [43], or faces [44,45]. As it had been previously noted by [32], the majority of the reviewed studies found evidence of greater exogenous attention to emotional than to neutral distractors.…”
Section: Plos Onementioning
confidence: 99%
“…For instance, a review by Yarrow et al (2009) concluded that sports experts show superior performance in perception, anticipation and decision making and that this superior performance is task specific and dependent on extensive practice. In addition, many other studies have revealed that sports experts outperform nonathletes in attention and memory for expertise-related tasks (Ericsson & Kintsch 1995;He et al 2018). Consequently, the advantages that sports experts hold in perception, attention and memory facilitate the extraction of information from expertise-related stimuli, causing them to perceive longer durations than nonathletes.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed from a given stimulus, the longer the perceived duration. Based on this proposal, sports experts, as a group with especially efficient information extraction in expertise-related tasks owing to their well-researched cognitive advantage (Ericsson & Kintsch 1995;Ericsson & Lehmann 1996;Feng et al 2017;He et al 2018;Wei & Luo 2010;Yarrow et al 2009), should perceive a longer duration than people who lack such expertise when they view an expertise-related stimulus. However, this prediction has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Regular engagement in sport and exercise improves general cognitive functioning and shapes the functional aspects of the human brain (Kramer and Erickson, 2007;Curlik and Shors, 2013). Previous studies have found that athletes perform better than non-athletes in behavioral tasks targeted at memory, attention allocation, attention flexibility, and executive function (Mann et al, 2007;He et al, 2018;Ishihara et al, 2018). Specifically, meta-analytic reviews have found that sports experts show faster and more accurate performance in regard to spatial memory, visual search tasks, and attentional paradigms (Mann et al, 2007;Voss et al, 2010).…”
Section: Discussionmentioning
confidence: 99%